PENGARUH MEDIA POHON HURUF TERHADAP KEMAMPUAN MEMBACA HURUF HIJAYYAH PADA ANAK USIA 5-6 TAHUN DI TK ISLAM BAKTI II KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Maya Paula Sari; Jaspar Jas; Daviq Chairilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study was to know the influence of the media tree letter to the child's ability to read letters hijaiyah in children aged 5-6 years in TK Islam Bakti II. The population in this study is children aged 5-6 years which consists of class A, amounting to 16 people and consists of 9 men and 7 women, the sampling technique used is saturated samples. Data analysis techniques used in this research is the analysis of the t-test, to see the influence of the media tree letter to the child's ability to read letters hijaiyah in children aged 5-6 years in TK Islam Bakti II. Data collection techniques in this study using observations. Data analysis techniques used in this research is the analysis of the t-test, to see the effect of tree games count towards kemampuanmengenal concept of numbers before and after treatment using SPSS forwindows Ver.17. based on the results of hypothesis testing is done, the result that the letter hijaiyyah tree media has a significant influence on improved reading skills hijaiyyah letter in children aged 5-6 years in TK Islam Bakti II District Tenayan Raya Pekanbaru. It can be seen from the results of tests of significance of this difference with the t statistic obtained t = 34.473, df = 15, and the error level of 5% = 2,042, then there is a table t in standard error (34.473> 2.042). Thus Ho rejected and Ha accepted. Results of the research hypothesis test results from the sample correlation, with a value before and after, significant value is 0,001. Therefore p <0.05 (0.001 <0.05).Keywords : Letter Tree, Reading Ability